Natural Dyes Plant And Processing Of Amarasi Woven Fabrics In The Village Of Tunbaun, West Amarasi District, Kupang Regency, East Nusa Tenggara - Nitti, Fransiska; Hardini, Junita; Pharmawati, Made (Metamorfosa: Journal of Biological Sciences, 2022)
This study aims to identify the types of plants, its parts that are used and the processing methods for amarasi weaving fabrics. Data collection in this study were carried out in of the village of Tunbaun, West Amarasi Sub-district, Kupang District, East Nusa Tenggara as one of the centers for the production of amarasi woven fabrics. Qualitative method was used in this study with interview, observation, documentation and literature study techniques. The results showed that the weaving craftsmen in Tunbaun village, used four types of plants as natural dye for weaving including noni root bark ( Indigofera tinctoria L., Fabaceae), indigo leaves ( Indigofera tinctoria L., Fabaceae), young teak leaves ( Tectona grandis L.f., Lamiaceae) and turmeric rhizome ( Curcuma domestica Val., Zingiberaceae). Processing of ground noni root bark, then boiled in water to get a red color. Indigo leaves are soaked for 2x24 hours, added lime and let with solution and allowed to stand for 24 to obtain a blue indigo paste. Young teak leaves are boiled in water until they get a purple color. While the turmeric rhizome is grated and then boiled in water to get a yellow color.   Keywords: Amarasi, Natural Dyes, Weaving